Analysis of optimization of retention pond function and sediment deposit projection in flood control in Palembang City, South Sumatra, Indonesia - Saputra, Erlianto Hona; Damiri , Nurhayati; Imanudin, Momon Sodik; Ngudiantoro, Ngudiantoro (Brawijaya University, 2025)
Palembang City frequently experienced flooding during the rainy season, necessitating effective urban water management strategies such as the development of retention ponds. This study employed several analytical methods, including erosion level assessment using the Universal Soil Loss Equation (USLE), sediment yield estimation through bedload traps and suspended sediment samplers, dead storage volume analysis by comparing storage capacities before and after sedimentation, sediment thickness rate calculation based on total erosion per unit area, and retention pond lifespan prediction using dead storage capacity, sediment discharge, and sediment specific weight. The results indicated extremely severe erosion rates ranging from 3,241 to 4,593 t/ha/year (>480 t/ha/year) and very high sediment yields between 4,368 and 7,018.5 t/year (>500 t/year). Sediment accumulation reduced storage efficiency, with dead storage volume reaching 44–61.11%. Siti Khadijah, RC reservoir, Talang Aman I, and IBA retention ponds were classified as having very large dead storage volumes, while Talang Aman II retention pond was in a large category. Sediment thickness rates ranged from 227.2 to 397.9 mm/year (>50 mm/year), indicating a very high sedimentation rate. Consequently, the estimated operational lifespan of the ponds was very short, between 1.86 and 6.36 years (<10 years). In conclusion, the retention pond areas in Palembang exhibited critical erosion and sedimentation issues, resulting in high sediment accumulation, reduced storage capacity, and significantly shortened pond lifespans. These findings highlight the urgent need for sustainable sediment management and maintenance strategies to enhance the effectiveness and longevity of urban retention ponds.